The Role of Graphic Design in Risk and Crisis Management - Mohamed, Mohamed Abdelaziz (Journal of Risk and Crisis Management, 2024)
In the context of risk management, the term “risk” refers to the uncertainties surrounding future events and can have a positive or negative impact. Risk management aims to identify, evaluate, prioritize and mitigate risks to minimize potential negative impact. The use of risk management is indispensable. It is impossible to implement any project without facing risks that may affect the progress of the project. This includes unexpected circumstances, situations and threats. Risk management aims to analyze these factors and make informed decisions about how to address, respond to or mitigate risks. In the art world, risk management plays a vital role in achieving creativity and success. risk management contributes to achieving a balance between creativity and realism, and enables artists to better achieve their goals. We must also remember that risks are not only negative. Some risks may carry positive opportunities to improve business processes or increase profits. Integrating “risk management” with “fine arts” seems an interesting challenge. Although the two sections seem contradictory at first, there are some intersections that can be explored. In areas such as theatrical performances or concerts, can help estimate risks related to live performances, such as physical injuries or technical accidents, as well as valuable cultural property. Such as paintings or historical collectibles, can be used to protect these properties from loss or damage, in addition to using risk management to estimate potential risks in marketing strategies for works of art, and think about how to deal with them effectively.
Keywords: Risk management; Fine Arts; Graphic Design